The Spike of SARS-CoV-2: Uniqueness and Applications - Kumavath, Ranjith; Barh, Debmalya; Andrade, Bruno Silva; Imchen, Madangchanok; Aburjaile, Flavia Figueira; Ch, Athira; Rodrigues, Diego Lucas Neres; Tiwari, Sandeep; Alzahrani, Khalid J.; Góes-Neto, Aristóteles; Weener, Marianna E.; Ghosh, Preetam; et al. (Frontiers in Immunology, 2021)
The Spike (S) protein of the SARS-CoV-2 virus is critical for its ability to attach and fuse into the host cells, leading to infection and transmission. In this review, we have initially performed a meta-analysis of keywords associated with the S protein to frame the outline of important research findings and directions related to it. Based on this outline, we have reviewed the structure, uniqueness, and origin of the S protein of SARS-CoV-2. Furthermore, the interactions of the Spike protein with host and its implications in COVID-19 pathogenesis as well as drug and vaccine development are discussed. We have also summarized the recent advances in detection methods using S protein-based RT-PCR, ELISA, point‐of‐care lateral flow immunoassay, and graphene-based field-effect transistor (FET) biosensors. Finally, we have also discussed the emerging Spike mutants and the efficacy of the Spike-based vaccines against those strains. Overall, we have covered most of the recent advances on the SARS-CoV-2 Spike protein and its possible implications in countering this virus.